Prevalence of bacteria isolated from patients with burn infection at a burn hospital in Baghdad and study of their antimicrobial susceptibility patterns - Hamed, Saad L.; Rasool, Khetam H.; Hussein, Nadheema H.; Taha, Butheina Mahamed (AL-Kindy College Medical Journal, 2016)
Background: The skin functions as a barrier to the external environment, damage to this barrier following a burn disrupts the innate immune system and increases susceptibility to bacterial infection. Objective: This study was carried out to determine the bacterial isolates and study their antimicrobial susceptibility in burned wound infections at one burn's hospital in Baghdad.Type of study:Cross-sectional study.Methods: The bacteria were identified at species level by using Analytic Profile Index (API) system and The antimicrobial susceptibility test was performed according to Kirby-Bauer (disk diffusion) technique.Results: Over a period of one year (from October 2014 to October 2015). Out of 848 patients with different degrees of burns, 186 (19.81%) positive bacterial isolates. Out of 186 bacterial isolates, the isolation rate of Gram positive was 14(7.53%) and Gram negative isolates was 172(92.47%). From those 172 Gram negative bacteria the most frequently isolated bacteria was Pseudomonas aeruginosa 60(32.26%) isolates followed by Acinetobacter baumannii 40(21.51) and all Gram positive bacteria were Staphylococcus aureus 14(7.53). The most effective antibiotic on Staphylococcus aureus isolates was Vancomycin (sensitivity rate was 11(92.86%)), while the highest resistance was to Penicillin and the rate of resistance was 14(100%) followed by Ampicillin 12(85.71%). The most effective antibiotic on Gram-Negative isolates was Imipenem (sensitivity rate was 165(95.93%)) followed by Amikacin (sensitivity rate was 146(84.88%)). On the other hand the Gram negative bacteria in this study were mostly resistant to Ampicillin 164(95.35%) and Amoxicillin-Clavulanic acid 157(91.28). Acinetobacter baumannii and Klebsiella pneumoniae isolates were the mostly resistant isolates than other gram negative bacteria under this study.Conclusion: Pseudomonas aeruginosa was the most frequently isolated bacteria among gram negative bacteria and the most effective antibiotics on Gram-Negative and Staphylococcus aureus isolates were Imipenem and Vancomycin, respectively.